Towards sustainable precision: A review of water jet meso and micromachining - Mohammad Ghasemian Fard; Akash Nag; Jana Petrů; Sergej Hloch (Results in Engineering, 2025)
Micro-Abrasive Water Jet Machining (µAWJM) has become a critical technology for precision micro-manufacturing, addressing the limitations of both conventional and other unconventional machining methods. Its significance lies in its ability to process complex geometries in a vast range of materials—including thermally sensitive polymers, brittle advanced ceramics, composites, superalloys, and thin-film structures—without inducing damage. As a non-thermal disintegration process, µAWJM holds a distinct advantage over methods like laser cutting and EDM by creating minimal heat-affected zones, thereby preventing the material degradation, warping, and residual stresses that often necessitate costly post-processing. This review provides a comprehensive analysis of µAWJM's fundamental principles, including fluid dynamics, abrasive particle behavior, and material removal mechanisms. It examines the intricate interplay of key process parameters such as abrasive particle size (MESH), nozzle geometry, fluid pressure, and standoff distance, and how these parameters influence machining performance and surface integrity. Recent technological advancements, including optimized abrasive delivery systems and the integration of machine learning for process optimization, are critically evaluated. This review not only highlights the inherent advantages of µAWJM but also addresses current challenges such as kerf taper, nozzle wear, and the efficient machining of novel materials. Furthermore, it delves into the diverse applications of µAWJM across microfluidics, biomedical engineering, aerospace, and electronics, showcasing its versatility in fabricating complex microstructures. Finally, this review outlines future research directions, ultimately solidifying µAWJM's crucial role in the future of sustainable and precise manufacturing.